Feasibility and Safety of Sodium Glucose Cotransporter-2 Inhibitors in Adults with Heart Failure after the Fontan Procedure. (9th December 2022) - Muneuchi, Jun; Sugitani, Yuichiro; Kobayashi, Masaru; Ezaki, Hiroki; Yamada, Hiromu; Watanabe, Mamie
Abstract : Sodium glucose cotransporter-2 (SGLT-2) inhibitors have been widespread in patients with heart failure; however, there is little information regarding its feasibility and safety among patients after the Fontan procedure. We presented five adults after the Fontan procedure who were treated with SGLT-2 inhibitors. All patients reduced oedema and/or pleural effusion despite other conjunct medications were ineffective. Although we did not measure the urine volume in all patients, all patients themselves reported an increase in urinary output after the administration of a SGLT-2 inhibitor. In addition, administration of a SGLT-2 inhibitor resulted in weight loss (4/5), an increase in systemic oxygen saturation (4/5), an increase in serum albumin level (4/5), an increase in estimated glomerular filtration ratio (4/5), and a decrease in plasma brain natriuretic peptide level (4/5). Our case series supported the feasibility and safety of SGLT-2 inhibitors in patients with Fontan circulatory failure, although the exact changes in urinary output were unknown in all patients. Further investigation will be required to explore a diuretic effect by SGLT-2 in patients after the Fontan procedure.